Citizen Science to Raise Antimicrobial Resistance Awareness in the Community: The MicroMundo Project in Spain and Portugal - Jessica Gil‐Serna; Patricia Antunes; Susana Campoy; Ángeles Cid; Antonio Cobo‐Molinos; Paulo Durão; Carmen Fajardo; Belén Fouz; Ana R. Freitas; Filipa Grosso; Piet W. J. deGroot; Trinidad deMiguel; et al. (Microbial Biotechnology)
ABSTRACT Antimicrobial resistance (AMR) poses a global threat to human, animal and environmental health. Among the multidisciplinary tasks aimed at collectively tackling the AMR crisis, surveillance, research and education stand as major priorities. Based on a crowdsourcing research strategy, the MicroMundo project, a partner of the Tiny Earth initiative in Spain and Portugal, has been developed and consolidated with success in the academic environment. The objectives are focused on promoting research and, especially, on bringing knowledge of One Health and microbiology concepts, as well as AMR awareness to the community. Following a service‐learning approach, MicroMundo integrates university and secondary/high school students in a citizen science‐based research project to collectively isolate microorganisms with the potential to produce new antibiotics from soil environments. Over the last 7 years, 32 MicroMundo hubs operating across 31 different Portuguese and Spanish universities have recruited thousands of teenagers in this quest. Here we review the outcome of this unprecedented effort from a scientific and an educational perspective.